Peran Psikologi dalam Penerapan Pendidikan Karakter pada Krisis Moral 2025 - Nayrafalsa Ardienda Putri; Salma Wafia; Gadiza Najla; Tara Alesha; Lukman El Hakim (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The moral crisis affecting today’s young generation in Indonesia has become a serious concern in the midst of globalization and digitalization. Traditional values are increasingly marginalized by the rise of instant gratification, hedonism, and individualism. This article explores the role of psychology in supporting the implementation of character education as a strategic solution to address this issue. Using a qualitative approach through literature review, the findings reveal that psychology plays a crucial role in shaping students’ character through understanding cognitive development, self-regulation, emotional intelligence, and experiential learning. However, challenges such as limited educator competence, weak collaboration between schools and families, and the negative influence of social media hinder the implementation process. Therefore, integrating psychological approaches with an adaptive education system is essential to foster a resilient and morally grounded generation.